PENERAPAN ECO-ENZYME SEBAGAI SARANA EDUKASI DALAM PENINGKATAN KEMAMPUAN PENGELOLAAN SAMPAH RUMAH TANGGA - Sudarti Ni Wayan; I Ketut Muada; Ni Putu Laras Purnamasari (Sewagati, 2025)
This community service program aims to provide education and training in eco-enzyme production as an effort to improve household waste management capabilities in the Banjar Prajasari area. The phenomenon of organic waste accumulation and environmental pollution is due to low public awareness regarding waste management. One simple, environmentally friendly product produced through the fermentation of fruit and vegetable waste that can be used as a versatile solution is known as Eco-enzyme. The Eco-enzyme production training was conducted through three activities: the first involved educational activities on household waste management, the second involved a hands-on eco-enzyme production workshop, and the third involved a twenty-day fermentation mentoring process. Data collection included observation, pre- and post-program knowledge assessments, and participant interviews. The results of the education and training on eco-enzymes showed a significant increase in public understanding of waste sorting, organic waste utilization, and eco-enzyme processing techniques. The community demonstrated positive behavioral changes in an effort to reduce household waste and successfully independently produce eco-enzymes. The conclusion of this activity is that community empowerment through the implementation of sustainable waste management activities and practical, effective, and efficient participatory education can increase public awareness in managing waste in the household environment. Keywords: eco-enzymes, household waste management, environmental awareness